Communicative Language Teaching (CLT): An Evolution in Revolution - ARIATNA ARIATNA (BAHAS, 2012)
The topic of language pedagogy has generated excitement and interest among language researchers for many years.  Again and again the discussion returns to the question of how to deliver language content to students so that they can learn a language effectively. Despite the numerous trends in language teaching, most attention has increasingly been given to an approach called ‘Communicative Language Teaching’ (CLT). As a new paradigm of pedagogy which  centres on communication-based classroom activities, CLT has emerged in response to an earlier focus on grammatical forms. This article is an attempt to briefly describe the beginnings of CLT and its developments, and to discuss different ideas surrounding CLT tenets and practice. In essence, this paper does not treat CLT as a superior western product but rather as an international phenomenon which attends to the needs of language learners in a variety of learning contexts.